Insulin's microvascular vasodilatory effects are inversely related to peripheral vascular resistance in overweight, but insulin‐sensitive subjects. (11th June 2013) - Hornstra, J.M.; Serné, E.H.; Eringa, E.C.; Wijnker, M.C.; de, M.P.; Yudkin, J.S.; Smulders, Y.M.
<x xml:space="preserve">Abstract</x> Objective The mechanisms underlying obesity‐related hypertension are incompletely understood. Microvascular dysfunction might play a role by increasing peripheral vascular resistance (PVR). Metabolic and microvascular effects of insulin are impaired in obesity, but how these impairments contribute to disturbed blood pressure homeostasis is unclear. Specifically, it is unknown whether local microvascular vasoactive effects of insulin play a role in determining systemic vascular resistance. The aim of this study was to investigate the association between PVR and local microvascular effects of insulin. Design and Methods Thirty‐seven healthy, overweight subjects (age 25‐55 years, BMI 25‐30 kg/m2) were cross‐sectionally studied. Local insulin‐mediated vasodilation was measured using skin laser Doppler fluxmetry combined with transcutaneous iontophoresis of insulin. For comparison, local vasodilatory effects of acetylcholine and sodium nitroprusside were measured. PVR was calculated from mean arterial pressure and cardiac output, assessed by pulse‐dye densitometry. Results PVR was inversely correlated with insulin‐mediated vasodilation (r = −0.50; P < 0.01). This finding was maintained after adjustment for age, sex, blood pressure, and smoking. PVR was not associated with local microvascular effects of acetylcholine. Conclusions Our study in overweight subjects suggests that insulin's role in the microvasculature may contribute to blood pressure control.